2019
DOI: 10.1093/mnras/stz1488
|View full text |Cite
|
Sign up to set email alerts
|

Planet-forming material in a protoplanetary disc: the interplay between chemical evolution and pebble drift

Abstract: The composition of gas and solids in protoplanetary discs sets the composition of planets that form out of them. Recent chemical models have shown that the composition of gas and dust in discs evolves on Myr time-scales, with volatile species disappearing from the gas phase. However, discs evolve due to gas accretion and radial drift of dust on time-scales similar to these chemical time-scales. Here we present the first model coupling the chemical evolution in the disc mid-planes with the evolution of discs du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 97 publications
3
87
0
Order By: Relevance
“…Such detailed comparison motivates the need for the development of more sophisticated models in two different areas. Firstly, detailed chemical evolution models for the evolution and transport of refractory and volatile elements in an evolving protoplanetary disc along the lines of those by Booth et al (2017); Booth & Ilee (2019) rather than just treating "gas" and "dust" as we have done in this work. Secondly, there is almost no understanding of the role of planet-disc interactions in controlling how different species may enter the gas and flow across the planetary gap, or be accreted by the planet's themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Such detailed comparison motivates the need for the development of more sophisticated models in two different areas. Firstly, detailed chemical evolution models for the evolution and transport of refractory and volatile elements in an evolving protoplanetary disc along the lines of those by Booth et al (2017); Booth & Ilee (2019) rather than just treating "gas" and "dust" as we have done in this work. Secondly, there is almost no understanding of the role of planet-disc interactions in controlling how different species may enter the gas and flow across the planetary gap, or be accreted by the planet's themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of nitrogen, Booth & Ilee (2019) find an enrichment of elemental nitrogen up to a factor of 2 above solar both within the NH 3 ice line and in an annulus just within the N 2 ice line. The high elemental nitrogen abundances within the NH 3 ice line are strongly dependent on the initial NH 3 abundance.…”
Section: Enriching Jupiter With Nitrogenmentioning
confidence: 93%
“…Recently there have been multiple studies that have looked at the effect of disk evolution, especially the growth and drift of icy grains, at the effect this has on the gas-phase elemental abundances (Ciesla & Cuzzi 2006;Booth et al 2017;Stammler et al 2017;Bosman et al 2018;Krijt et al 2018;Booth & Ilee 2019). In general, it is found that enrichments above solar abundances in a certain element can happen just inside an ice line if radial drift is efficient and the ice line corresponds to a species that is an abundant ( 10%) carrier of that element.…”
Section: Enriching Jupiter With Nitrogenmentioning
confidence: 99%
“…Since the early work of Öberg et al (2011), several studies have been devoted to understanding the link between the abundances of the two most abundant high-Z elements, carbon (C) and oxygen (O), and the planetary formation process; for more recent discussions, see, e.g., Madhusudhan et al (2016), Mordasini et al (2016), Booth & Ilee (2019), Cridland et al (2019), and references therein. Recently, a few studies have taken a first look at nitrogen (N), as well (Bosman et al 2019;Öberg & Wordsworth 2019).…”
Section: Introductionmentioning
confidence: 99%